Digital Career Planning Models for Z Generation - Umar, Nur Fadhilah (Indonesian Journal of Educational Studies, 2020)
Abstract. In this study, career planning is one aspect of human development that lasts a lifetime. So that everyone needs to plan a career according to talents, interests, and potential. Based on Gardner's theory of multiple intelligence, everyone has several intelligence types that develop as a reflection of their talents, interests, and potential in solving problems. Generation Z as the generation that dominates in the digital technology era with unique and different characteristics from the previous generation, generation Z career planning needs to be implemented specifically. Therefore, this research aims to develop a valid and acceptable career planning model for Generation Z. This type of research is development research using the Borg & Gall (2003) development model. The career planning model for generation Z was validated by three guidance and counseling experts. The instrument used was a validity and acceptability test instrument consisting of aspects of feasibility, usability, content, appearance, and language. The results showed that the digital career planning model is valid and acceptable to be used and tested in small groups, namely users of the career planning model, namely counseling teachers and junior high school students.Â